2015
DOI: 10.1053/j.gastro.2014.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Molecular Subtypes of Colorectal Cancer and Patient Survival

Abstract: Background and Aims. Colorectal cancer (CRC) is a heterogeneous disease that can develop via several pathways. Different CRC subtypes, identified based on tumor markers, have been proposed to reflect these pathways. We evaluated the significance of these previously proposed classifications to survival. Methods. Participants in the population-based Seattle Colon Cancer Family Registry were diagnosed with invasive CRC from 1998 through 2007 in western Washington State (n=2706), and followed for survival throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
316
6
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(351 citation statements)
references
References 47 publications
26
316
6
3
Order By: Relevance
“…In contrast, those patients whose tumours were MSS and mutated KRAS or BRAF exhibited poor 5-year DFS rates. Phipps and colleagues investigated the association between CRC subtypes and survival in a large population-based registry cohort of patients (Phipps et al, 2015). They found that DFS and OS for patients with MSI CRC that was KRAS-mutated or BRAF-mutated (but not for double wildtype patients) were significantly better than similarly mutated MSS tumours.…”
Section: The Implications Of Kras and Brafmentioning
confidence: 99%
“…In contrast, those patients whose tumours were MSS and mutated KRAS or BRAF exhibited poor 5-year DFS rates. Phipps and colleagues investigated the association between CRC subtypes and survival in a large population-based registry cohort of patients (Phipps et al, 2015). They found that DFS and OS for patients with MSI CRC that was KRAS-mutated or BRAF-mutated (but not for double wildtype patients) were significantly better than similarly mutated MSS tumours.…”
Section: The Implications Of Kras and Brafmentioning
confidence: 99%
“…This method imputes missing data while acknowledging the uncertainty associated with the imputed values and provides valid statistical inferences under the missing at random (MAR) assumption. 41,42,43 Indeed, when data are MAR, analyses based on complete cases may be biased because cases with missing values may differ systematically from the completely observed cases. In our study, results obtained using multiple imputations or a complete case approach were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Általánosságban a fogazott útvonalon kialakuló vastagbéldaganat agreszszívebb viselkedésű és rosszabb prognózisú, mint a klaszszikus útvonalon létrejövő CRC. Több vizsgálatban az OS és a DFS -és néhány vizsgálatban a CSS tekintetében is -a molekuláris besorolás szerinti 2-es típusú (CIMP-H/MSI-L/MSS) daganatok bizonyultak a legkedvezőt-lenebb prognózisúnak, melyek a fogazott útvonal képvi-selői [37]. Az egyes biomarkereket külön vizsgálva az MSI-H-fenotípus önmagában számos vizsgálatban kedvező prognosztikai faktornak bizonyult.…”
Section: Prognózisunclassified